2019
DOI: 10.1176/appi.neuropsych.18040086
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Emotion Recognition as Markers of Frontal Behavioral Dysfunction in Amyotrophic Lateral Sclerosis

Abstract: Background: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease with prominent motor symptoms. ALS patients may also manifest frontal behavior and cognitive decline, including impairment in facial emotion recognition. We aimed to investigate whether deficits in emotion recognition are associated with frontal behavior symptoms in ALS. Methods: We enrolled two groups of participants: 1) patients with probable or definite sporadic ALS (n= 21, 11 male/10 female; median age 62 years-old; median disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…ALS sample sizes are relatively small in most studies: only one study has more than one-hundred patients [25]; four studies have 50-100 included patients [2,16,26,27]; nineteen studies have 20-50 patients [9,18,19,24,[28][29][30][31][32][33][34][35][36][37][38][39][40][41]; thirteen studies recruited 10-20 ALS patients [21][22][23][42][43][44][45][46][47][48][49][50][51]; two studies had 2-10 patients [52,53]. Two were single case studies [17,20].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…ALS sample sizes are relatively small in most studies: only one study has more than one-hundred patients [25]; four studies have 50-100 included patients [2,16,26,27]; nineteen studies have 20-50 patients [9,18,19,24,[28][29][30][31][32][33][34][35][36][37][38][39][40][41]; thirteen studies recruited 10-20 ALS patients [21][22][23][42][43][44][45][46][47][48][49][50][51]; two studies had 2-10 patients [52,53]. Two were single case studies [17,20].…”
Section: Resultsmentioning
confidence: 99%
“…Some articles showed in ALS with cognitive or behavioral impairments subgroups lower performances than control participants in emotion recognition tasks, while the ALS total group was not impaired [35,36]. Differently, other studies found a similar proportion of patients with and without cognitive/behavioral deficits among those who presented impaired recognition of emotions according to facial expressions or story-based emotion recognition tests [23,31].…”
Section: Relationship Between Emotional and Clinical Aspectsmentioning
confidence: 96%
See 2 more Smart Citations
“…This finding is consistent with previous studies, which reported decreased GM volume and thickness in several brain regions, including the SFG and STG [25,26] Functionally, the SFG, which is located in the dorsolateral prefrontal cortex, has been shown to play a crucial role in working memory [27] and attention [28] The STG has been involved in speech perception [29] and emotion recognition [30] In ALS, a number of studies have reported varying degrees of impairments in the language, cognitive, and behavioural domains, such as frontal executive deficits that involve verbal fluency, attention, and working memory [31,32] and facial or prosodic emotion recognition deficits, especially for disgust and surprise [33,34] The finding of significant cortical thinning in the SFG and STG might be the anatomical substrate underlying such nonmotor impairments in patients with ALS and adds further evidence for a continuum between ALS and frontotemporal dementia.…”
Section: Cortical Thinning In Alsmentioning
confidence: 99%